Atividade fotocatalítica do TiO2 e do sistema core-shell CoFe2O4@TiO2 obtidos pelo método Pechini modificado - Neris, Alex de Meireles (2014)
The need to control textile effluents due to contamination of rivers has led CONAMA to regulate and require a more efficient treatment process. Among the methods of treatment, heterogeneous catalysis stands out due to its high efficiency. The most used photocatalyst is TiO2. The combination of this material with other ones has been employed to improve its activity and/or its performance. Several systems have been tested, including the core-shell that constitutes a complete coverage of one material by another. In this work, TiO2@CoFe2O4 was synthesized by the modified-Pechini method with the addition of CoFe2O4 nanoparticles into the polymeric resin containing titanium. A magnetic material was obtained, which was characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), ultraviolet - visible spectroscopy (UV-Vis), specific surface area by the BET method. The materials were applied in the photodiscoloration of an azo dye. The pure TiO2 calcined at 700 °C showed a mixture of phases anatase / rutile in the proportions 77/23%, which was the calcination temperature which led to the highest photocatalytic activity in the discoloration of the solution yellow gold remazol (RNL). A discoloration of 81% in color of the solution was attained after 6 h of exposure to UV light, while 94% was reached after 2 h of irradiation with sunlight. With the core@shell system CoFe2O4@TiO2 synthesized with 90 % of TiO2, a mixture of anatase and rutile of 92 : 8% was obtained for a calcination temperature of 500 °C. This material showed 76% discoloration after 16 h of exposure to UV light under the same conditions used for the test with pure TiO2